(untitled) (Research, Society and Development, 2022)
Considering the presence of the theme in the media with dissemination of images of black holes and the measurement of gravitational waves, it became relevant to approach the concepts of Contemporary Physics, still in High School. However, such concepts are not intuitive like most of Classical Physics subjects and usually appear in the final chapters of textbooks for the third year of high school and, sometimes, it is little explored. This article proposes a lesson plan prepared from the methodological perspective of the flipped classroom proposed by Bergmann & Sams (2018) and the use of the Interstellar movie as a teaching tool to address topics related to the Special and General Theory of Relativity and the theme around black holes. The lesson plan was designed for application in a third year high school class and structured in three moments: (i) before class: watching the movie Interstellar, Youtube videos selected by the teacher and reading a chapter of the textbook related to the theme, (ii) classroom debate with the teacher’s mediation; and, (iii) carrying out tasks and evaluation. It is a flexible proposal adaptable to any content that takes into account the interest of students, current topics in the field of Physics and its approach in different contexts and scientific applications of physical phenomena in science fiction films, as seen in the Interstellar movie.